Comparative analysis of the Streptococcus pneumoniae competence development in vitro versus in vivo during pneumonia-derived sepsis - Chong, Sook Yin; Lew, Shi Qian; Alam, Tauqeer; Gaulke, Christopher A.; Lau, Gee W. (Frontiers in Microbiology, 2025)
IntroductionThe Streptococcus pneumoniae (pneumococcus) competence regulon is well-known for regulating genetic transformation but is also important for virulence. Some pneumococcal strains can enter a transient competent state for genetic transformation in an optimized competence-inducing medium when the threshold level of the peptide pheromone competence stimulating peptide is attained; upregulating the expression of three distinct phases of “early”, “late” and “delayed” competence genes. Recently, we discovered that pneumococcus can naturally enter a prolonged competent state during acute pneumonia in mice. However, mechanisms driving competence development during host infection are rarely examined, and a direct comparison between in vitro and in vivo competence induction has not been performed.MethodsWe conducted a comparative gene expression analysis of pneumococcal competence development in vitro versus in vivo during pneumonia-derived sepsis in mice. We examined existing RNA-Seq data and performed validation using RNA obtained from an independent replicate experiment.Results and discussionOur analysis revealed both similarities and differences in the expression of “early”, “late”, and “delayed” competence between in vitro versus during pneumonia-derived sepsis. Our results may reveal new aspects of pneumococcal competence biology.